Between Ibn Al-Jawzi and Al-Qurtubi - A Balancing Study Between Their Interpretations - (Islamic Sciences Journal, 2023)
ABSTRACT                             This study aims to explain the approach of the two  interpreters imams Ibn Al-Jawzi and Al-Qurtubi, may Allah Almighty bless them and his mercy. Allah Almighty has honored us in this research to stand with these two imams in two topics: The first includes two demands. The first demand:  to introduce Imam Ibn A-Jawzi, may Allah have mercy on him. The second demand: to introduce  study of a balance between the two interpretations, and it included the belief of each of them and their approach to interpretation, their martyrdom of the Israelites and their sources, and the method followed by each of them in presenting the interpretation material, and then the conclusion came to record the most important results of the research and praise be to Allah, Lord of the Worlds.